More than 16 Years, More than 16 Stressors: Evolution of a Reflective Gravel Beach, 1989-2005 - Catto, Norm (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractMobile Beach, a reflective, moderate-to-high energy, gravel bayhead bar system in eastern Newfoundland, has been influenced by 15 hurricanes and strong winter storms, and at least 9 significant autumn and winter storms between July 1989 and December 2005. Yearly variations in the extent of seasonal ice cover offshore, and snow cover, ice foot development, and freezing of beach sediment, also have shaped Mobile Beach. Vehicle activity and foot traffic have resulted in coarsening, compaction, and steepening. Excavation of a drainage channel through the beach affected sediment supply and transport. Changes in hurricane activity, in the occurrence and impact of northeast winds, and in seasonal ice cover, play a major role in shaping coastal morphology, in conjunction with sea level rise. Variations in the North Atlantic Oscillation are reflected in storm effectiveness and snow and ice influence. Tropical storm and hurricane activity results in substantial modifications to the beach, but the erosional events cannot be correlated with overall variations in hurricane activity. Although Mobile Beach does respond to large-scale regional to hemispheric factors, local factors, including the angle of wave attack, the number of previous events, and anthropogenic activity, play the dominant role here.